Indirect effect of psychological capital by using Partial Least Square (PLS) path analysis - Nanthini Balu; Maya Rathnasabapathy (MethodsX)
Understanding the relationship between Learned Helplessness (LH) and Psychological Capital (PsyCap) is essential for developing effective interventions for Indigenous adolescents. This study explored the role of PsyCap as a mediator in the link between LH and Psychological Well-Being (PWB). Total of 173 Indigenous adolescents (85 boys and 88 girls) from sixth to eleventh grade at government residential schools. Smart Partial Least Squares (PLS) software used for Path analysis and the results showed that the average variance extracted (AVE) values for LH (0.658), PsyCap (0.733), and PWB (0.681) were exceeded the Fornell-Larcker criterion for discriminant validity. The variance accounted for (VAF) indirect effect was 41.3 %, suggesting partial mediation. PsyCap partially mediated the relationship between LH and PWB (β = -0.239, p < 0.01) with a 95 % confidence interval. These findings highlight the significant contribution in the field of psychology to find out the indirect effects by using Partial Least Square path analysis in illustrated graphical setting.Major Findings • Measurement model of LH and PsyCap on PsyCap indicate strong Cronbach alpha and AVE of convergent validity. • Structural model indicates that collinearity statistics (VIF) of inner model matrix and list shows that required significant values. • Path analysis of LH→ PsyCap→ PWB shows significant Beta value.